WHOLE GENOME SEQUENCING OF ENTEROBACTER CLOACAE SM32 IN THE FIRST ISOLATION OF THE MEDICAGO SATIVA L. ROOT NODULES IN MOSUL, IRAQ CAPABLE OF PRODUCING INDOLE-3-ACETIC ACID - S. M. Mohammed; R. H. Sultan; V. Edavana (مجلة الأنبار للعلوم الزراعية)
Seven rhizobacterial isolates from the root nodules of several leguminous plants were obtained from various cultural areas in Mosul, Iraq for this study. The SM21 and SM32 isolated from Medicago sativa L., SM27, SM30, and SM43 from Trifolium alexandrinum L., and SM1 and SM33 from Vigna unguiculata L were used to determine which could produce indole-3-acetic acid. After 3-days incubation in an LB liquid medium, the SM32 isolate produced a maximum output of 21.43 g mL1-. It reached 72.96 g mL1- with an ideal tryptophan content of 3 mg mL-1 supporting the process. The molecular characteristics of the SM32 rhizobacteria isolate, with a total genome length of 4,583,676 base pairs, were similar to those of E. cloacae. There were 4,348 CDSs altogether that were coded for proteins, and 75 RNA genes. This first version of the full genome shotgun sequence of E. cloacae SM32 was deposited at the DDBJ/ENA/GenBank under accession number JBEFMZ000000000 (BioProject accession number PRJNA1121377 and BioSample accession number SAMN41748806). The NCBI Prokaryotic Genome Annotation Pipeline (PGAP) added the annotation